HOMOGENITAS KARAKTER DAN TRADISI KEAGAMAAN MASYARAKAT PEDESAAN DI KOTA CILEGON - sujai, ahmad (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2017)
Madrasah as the oldest Islamic educational institution after boarding school has been recognized to have a very big contribution to the religious behavior of Islamic society in Indonesia. Madrasah Al-Jauharotunnaqiyyah Cibeber is one of the madrassas that has been established since 1924, which contributed in the birth of alumni-alumni who are competent in the field of religion scattered in the region of Banten and surrounding areas. In this study the authors find out, whether there is the role of alumni madrasah Al-Jauharotunnaqiyyah cibeber in shaping the character homogeneity of religious and cultural rural communities in the district area cebeber cilegon city. Based on the results of research that has been done in rural communities Cibeber District Cilegon City which consists of 6 villages, namely: Cibeber Village, Kedaleman, Karangasem, Kalitimbang, Bulakan and Cikerai Village, it can be concluded that alumni madrasah Al-Jauharotunnaqiyyah Cibeber very instrumental in forming homogeneity Religious and cultural rural communities. The ways and methods used by alumni in shaping the homogeneity of the religious and cultural character of rural communities is to teach, preach and exemplify religious teachings /values ​​on the rural community